Formulation, preparation, and sensory evaluation of meat hamburger from culling goats with different fat contents - Soedirlan Resosemito, Franky; Carlos Quadros Morais, José; Layane Salazar Queiroz, Taisa; das Chagas da Silva Ferreira, Francisca; Furtado Teixeira Belfort, Cleidiana; Jefferson Reis da Silva, Wendel; Ellen Castro Sousa, Andressa; Laércio Silva Pastor de Araújo, Micael (Seven Editora, 2023)
The main objective of this work is to develop and evaluate hamburger sorcesensorially using goat meat from discarding animals with different levels of pig fat. Meat from discarded goats from adult animals without distinction of breed, obtained from the integral bone of the whole carcass, was cut into small blocks and ground together with pork bacon (in the proportion of 10%, 15% and 20% of the meat mass) in 6 mm discs. Meat, fat and other ingredients were placed in a mixer and molded in hamburger form and frozen in a freezer at –18°C. The burger was served after roasted in margarine, such as commercial hamburger, cubed on its side. 1,5 cm The intention of purchase and frequency of consumption were analyzed, in addition to the opinion about the color, odor, texture and flavor of the product. According to the results, it can be said that the F3 of the goat hamburger was better evaluated by the judges, both for the sensory properties and for the intention of purchases. The good acceptability and purchase intention of 74.5 % of the tasters confirm the technological potential of meat from discarding goats. This result is due to the greater softness and juiciness due to the presence of satisfactory fat in the formulation. As the discard meat is a low cost raw material, the preparation of hamburgers allows a better use of them, diversification the products offered, adding value to the product and contributes to the improvement of income of producers and consequent development of agribusiness. DOI: https://doi.org/10.56238/tfisdwv1-127